The Relationship between Pre-service EFL Teachers´ self-confidence and language performance - Chimbo Jácome, Kerly Jacquelin; dos Santos, Jardel Coutinho (Arandu UTIC, 2025)
This study explores the relationship between self-confidence and linguistic performance in pre-service English as a Foreign Language (EFL) teachers. Self-confidence influences participation, anxiety, and communication in language learning. Using a mixed-methods approach, including surveys, observations, and interviews, the study examines the experiences of students in their seventh level of training at a public university in Ecuador. Findings show that many struggle with speaking English in public due to fear of making mistakes, leading to hesitations, reduced participation, and difficulties with fluency and pronunciation. Personal experiences, emotions, and external feedback shape their confidence levels. While some show resilience, others experience linguistic insecurity, affecting their overall performance. The study highlights the need to create supportive environments that encourage risk-taking, offer constructive feedback, and promote collaborative learning. It also emphasizes addressing emotional factors in teacher training programs to help future educators develop their linguistic competence with confidence, ultimately benefiting their students’ language learning.